Periodic Law and Periodic system of chemical elements - L. Yu. Alikberova (Тонкие химические технологии, 2009)
The earliar attempts chemical of elements' classifications were usually based on their properties. Since chemical properties are very complex and diverse, so that classifications were unsuccessful. The first step to creation Mendeleev's periodic system for chemical elements became using of related atomic weights.